Using ontology to enhance requirement engineering in agile software process - Sitthithanasakul S. (2017)
© 2016 IEEE. One of the most important factors when determining the success of the Agile software development process is requirement engineering. Ontology is a well - known knowledge representation tool in knowledge management application. This paper contributes the investigation of its usage in the software development process. We propose the novel use of ontology to enhance requirement engineering in the Agile process to improve communication between software development team and stakeholders.